Chapter Da un segno a tanti segni. L'emergere della polisemia del termine disegno nelle traduzioni tedesche delle Vite di Vasari - Ballestracci, Sabrina (Lessico multilingue dei Beni Culturali, 2023)
This chapter focuses on the German translations of La Vita of Raffaello by Vasari. Ballestracci focuses her attention on translations into German of the word «disegno», on its complex and multifaceted meanings and its crucial role in Vasari's work. After presenting all the occurrences of the word forms from the lemma «disegn-», Ballestracci analyses the instances in which «disegn-» was not translated directly as «Zeichnung» in two different target texts. Results of this study confirm the fascinating hypothesis by which the translations of a polysemous term cause the surfacing of meanings in the target text that were hidden in the source text and that, in this particular case, carry key aspects of Vasari's thought.